Some of Hematclogical and Biochemical Parameters of Children Infected with Anemia in Samawa City - Resan Ibraheem, Ihsan (University of Thi-Qar Journal of Science, 2009)
Anemia spreads a widely in many countries in the world particularly the poorand developing countries . Iraq is one of these countries and many of children sufferfrom bad environmental health , and economic conditions . Samples of blood collectedfrom patients infected with anemia in the hospital of children and delivery insamawah city . Hematological and biochemical parameters were determined ,hematological parameters included packed cell volume , hemoglobin concentration ,total white blood cells count while biochemical parameters included glucose ,cholesterol , billrubin and urea concentrations were measured . Results showed High significant increase (P<0.01) in the number of childreninfected with iron deficiency anemia in comparison with other types of anemia , sonumber of children infected with sickle cell anemia and hemolytic anemia . Also therewas high significant decrease (p<0.01) in hemoglobin concentration and packed cellvolume in all types of anemia in comparison with a control group Glucose andbilirubin increased significantly (p<0.01). Total white blood count increasedsignificantly (p<0.01) in patients with thallasemia . sickle cell anemia and hemolyticanemia compared with patients with iron deficiency anemia and a control group .Total serum cholesterol high significant decreased (p<0.01) in all types of anemiacompared with a control group . Results showed there were non significant differencesin urea levels in all types of anemia compared with a control group.